Laboratory testes with quality data in Dentistry - Campos, Juliana Alvares Duarte Bonini [UNESP]; Oliveira, Ana Luísa Botta Martins de; Santos, Patrícia Aleixo do; Oliveira, Ana Carolina Botta Martins de; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (My University, 2013)
In laboratory tests, just following the manufacturer’s instructions of materials or equipments may not be enough to obtain reliable data. Thus, intra and inter-examiners studies may be required. The aim of this study was to illustrate the application of the Intraclass Correlation Coefficient (r) in a study related to the color changing and hardness of composite resin conducted by two examiners. The color and hardness of 10 specimens of composite resin were evaluated by a colorimetric spectrophotometer and hardness tester, respectively, at two different times. Two trained examiners performed two measurements with an interval of one week. Specimens were stored in artificial saliva at 37±1ºC for 7 days. The Intraclass Correlation was used for analysis of intra and inter-examiner reproducibility. The intra-examiner reproducibility was 0.79, 0.44 and 0.76 for L, a and b color coordinates for the examiner 1 and 0.84, 0.23, 0.21 for examiner 2. For hardness, r-values were 0.00 and 0.23 for the examiner 1 and 2, respectively, showing unsatisfactory agreement on color and hardness evaluation for both examiners. It was noted that only the observation of protocol for use of equipment and examiners training were not sufficient to collect reliable information. Thus, adjustments in the experimental protocol were made and devices were produced to standardize the measurements. The reproducibility study was performed again. For examiner 1, values as 0.90, 0.59 and 0.79 were verified for L, a and b coordinates and, for examiner 2 were obtained values of 0.90, 0.75, 0.95. In relation to hardness, r-values of 0.75 and 0.71 were obtained for examiners 1 and 2, respectively. The inter-examiner reproducibility was 0.86, 0.87, 0.91 for L, a and b coordinates and 0.79 for hardness. It was concluded that intra and inter-examiner calibration is essential for obtaining quality measurements in laboratory tests.
Keywords: Reproducibility of results; Laboratory research; Dentistry